MODEL PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI ORGANIZATIONAL LEARNING DAN DONATING KNOWLEDGE SERTA COLLECTING KNOWLEDGE - Firdaus Nugroho Adi Saputro (Jurnal Ekonomi dan Bisnis, 2017)
This study aims to determine the effect of organizational learning and knowledge Donating andcollecting knowledge on teacher performance in SMA Islam Sultan Agung 1 Semarang. In thisstudy proposed several variables, namely organizational learning as independent variables,the performance of human resources as the dependent variable, as well as collecting Donatingknowledge and knowledge as an intervening variable. This type of research in this study isexplanatory research and using research methods to the census of 60 teachers in SMA IslamSultan Agung 1 Semarang. The first phase tested the validity and reliability questions foreach variable. The second stage regression test organizational learning, knowledge donatingand collecting knowledge on teacher performance. The results in this study were all positivesignificant variable, except for the variable of organizational learning negatively influencesignificantly to the performance of human resources in SMA Islam Sultan Agung 1 Semarang.Keywords: Organizational Learning, Knowledge Donating, Knowledge Collecti ng,Performance Human Resources